Correction: Discovery of 4, 6-disubstituted pyrimidines as potent inhibitors of the heat shock factor 1 (HSF1) stress pathway and CDK9. See DOI: 10.1039/c6md00159a. Issue 9 (7th September 2016) - Rye, Carl S.; Chessum, Nicola E. A.; Lamont, Scott; Pike, Kurt G.; Faulder, Paul; Demeritt, Julie; Kemmitt, Paul; Tucker, Julie; Zani, Lorenzo; Cheeseman, Matthew D.; Isaac, Rosie; Goodwin, Louise; et al.
Abstract : Correction for 'Discovery of 4, 6-disubstituted pyrimidines as potent inhibitors of the heat shock factor 1 (HSF1) stress pathway and CDK9' by Carl S. Rye et al., Med. Chem. Commun., 2016, 7, 1580–1586.